OPPORTUNITIES AND THREATS OF USING ARTIFICIAL INTELLIGENCE IN MARKETING (Marketing Journal, 2025)
This article examines the application of artificial intelligence technologies in the field of marketing, their current state, and development trends. The main directions, opportunities, and existing threats of using artificial intelligence in developing and implementing marketing strategies are analyzed. The effectiveness of artificial intelligence technologies in customer relationship management, marketing research, content creation, and implementation of personalized marketing campaigns is evaluated. Promising directions and problems of using artificial intelligence in the field 103 of marketing in Uzbekistan are identified, and recommendations for their solution are given.
Keywords: artificial intelligence; marketing; digital marketing; machine learning; big data; customer experience; content automation; marketing analytics; personalization; ethical issues